Influence of ethnic origin, gender and religion on employment and labor relations - Ryazantseva, Margarita V.; Mikhaylova, Natalia V.; Sokolovskiy, Konstantin G.; Kolomoets, Elena N.; Zatsarinnaya, Еlena I. (Opción, 2020)
The article outlines key reasons that have caused discrimination taking care of all socially vulnerable groups via comparative qualitative research methods. In addition, new criteria and approaches are suggested for review within the policy of a socially-oriented staff. As a result of the analysis of provided works, there is a lack of or very poor integration in the up-to-date labor world, taking into account the relevance of researched indicators in a country. In conclusion, the study and implementation of experience on equality issues is a necessary measure, which can have a positive impact on solving of this labor-intensive process.